Outcome of patients ≥ 60 years of age after alcohol septal ablation for hypertrophic obstructive cardiomyopathy - Jahnlová, Denisa; Tomašov, Pavol; Adlová, Radka; Januška, Jaroslav; Krejčí, Jan; Dabrowski, Maciej; Veselka, Josef (Archives of medical science, 2019)
INTRODUCTION: The outcome of patients ≥ 60 years of age after alcohol septal ablation (ASA) for obstructive hypertrophic cardiomyopathy (HCM) remains unresolved. We sought to determine the long-term survival and the causes of death in this population. MATERIAL AND METHODS: We enrolled 156 consecutive patients (69 ±6 years, 69% women, follow-up: 4.8 ±3.5 years) who underwent ASA at ≥ 60 years of age. RESULTS: The 30-day mortality rate was 1.3%. At the last check-up, 81% of patients were in New York Heart Association class ≤ 2 and 76% had a left ventricular outflow tract gradient (LVOG) ≤ 30 mm Hg. A total of 39 patients died (51% of cardiovascular causes, 44% of non-cardiovascular causes, 5% of unknown causes) during the 734 patient-years. The annual sudden mortality, the sudden mortality and the all-cause mortality rates were 0.5%, 1.1%, and 4.8%, respectively. The all-cause mortality was higher compared to the age- and sex-matched general population (p = 0.002). CONCLUSIONS: Alcohol septal ablation was safe and effective in the long-term follow-up. We observed a reduced life expectancy compared to the age- and sex-matched general population. Mortality was almost equally due to cardiovascular and non-cardiovascular causes of death.
Keywords: sudden cardiac death; survival; hypertrophic cardiomyopathy